Preparation Of Future Chemical Chemistry Teachers for Preparation for International Research - Shernazarov Iskandar Ergashovich (Zien Journals, 2022)
The article presents contextual tasks aimed at developing the skills of performing work tasks in the programs of international assessment of future chemistry teachers, the concept of improving the literacy of future chemistry teachers for the preparation of these tasks
Keywords: natural science literacy; reading literacy; mathematical literacy